PENGEMBANGAN KEMAMPUAN LITERASI MATEMATIS MELALUI MODEL PJBL DENGAN PENDEKATAN REALISTIC SAINTIFIC DAN PENGUKURAN BERBASIS PISA - Utami, Citra; Nirawati, Resy (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
The aim of this research is to gain the validity, practicality, and effectiveness of developing instructional sets of mathematics through PjBL learning with realistic saintific approach and PISA-based measurements and to describe students' mathematical literacy skills in terms of KAM aspects and PISA measurement process. The development research using modified Plomp model. The tools developed include RPP, LAS, and TKLMBP. Data processed by -test, the proportion of -test, and gain test. The results showed: (1) The instructional sets PjBL model with realistic scientific approaches and PISA-based measurements to develop students' mathematical literacy skills is validity, practicality, and effectiveness; (2) The ability of students' mathematical literacy to based on the KAM aspects obtained in the three KAM groups is statistically significantly increased; and (3) students' mathematical literacy skills to based on aspects of PISA measurement, most students can solve problems that are in accordance with aspects of PISA measurement.